Vehicular impact as a source of wildlife mortality in the Western Pacific Coast of Mexico - Carlos Delgado-Trejo; Rubén Herrera-Robledo; Nabil Martínez-Hernández; Cutzi Bedolla-Ochoa; Catherine E. Hart; Javier Alvarado-Díaz; Ireri Suazo-Ortuño; Héctor Nava-Bravo; Leonel Lopez-Toledo; Eduardo Mendoza (Revista Mexicana de Biodiversidad)
Road construction produce abrupt changes in landscape topography, microclimate, vegetation cover and levels of traffic noise. Moreover, road networks negatively affect vertebrate abundance, population gene flow, animal behavior and individual survival. Between July 2010 and January 2011, we conducted 10 surveys of animals killed on a road in Michoacán, Mexico. We recorded a total of 314 animals killed which included: 15 species of reptiles, 13 of mammals, 9 of birds, and 1 amphibian. Mammals were the most impacted accounting for 65% of the road kills followed by reptiles (25%). Mortality concentrated on road sections combining low sinuosity with high forest cover. Of the 15 reptile species recorded, 6 were endemic and 10 were listed as globally threatened or subject to special protection in Mexico. Road killed mammals also included species of conservation concern, 3 of which were endemic to Mexico. Our findings confirm that roads are a major mortality source for wild fauna. Strategies are greatly needed, at the global and local level, to mitigate the impact of roads on biodiversity.